2014
DOI: 10.1155/2014/901371
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Combined with Angiotensin-2 Type-1 Receptor Antagonists Induces More Necrosis: A Murine Xenograft Model of Renal Cell Carcinoma

Abstract: Background. Angiotensin-2 type-1 receptor antagonists not are only antihypertensive drugs but also can inhibit VEGF production. We hypothesised that adding telmisartan to sunitinib could potentiate the antiangiogenic effects. Material and Methods. 786-O cell lines were injected in nude mice. After tumor development, mice were divided into 4 groups: the first was the control group (DMSO), the second group was treated with sunitinib alone, the third group was treated with telmisartan alone, and the fourth group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…(29, 30) Physiologic concentrations of sunitinib are near 10 μM. The combination of sunitinib with captopril decreased cell viability to 59.3%, 48.1%, and 36.8% at 10, 100 and 1000 μM concentrations in A-498 RCC cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(29, 30) Physiologic concentrations of sunitinib are near 10 μM. The combination of sunitinib with captopril decreased cell viability to 59.3%, 48.1%, and 36.8% at 10, 100 and 1000 μM concentrations in A-498 RCC cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…(4) Recently, Verhoest and colleagues reported that combination therapy with sunitinib and telmisartan, an ARB, resulted in slower tumor growth, increased tumor necrosis, decreased central microvascular density, and decreased circulating VEGF levels in a murine xenograft model of RCC. (30)…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that an anti-RAS agent can enhance the effect of sunitinib in a murine xenograft tumor model. 35 Although NO donors such as nitrates or phosphodiesterase 5 inhibitors may also be beneficial, it has been suggested that these agents may potentially compromise the antiangiogenic effect and therefore they can best be avoided. 22 The knowledge that activation of the endothelin-axis is involved in the hypertension induced by angiogenesis inhibition may also favor the use of endothelin receptor blockers in angiogenesis inhibitioninduced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine xenograft model of RCC, the combination of sunitinib and telmisartan, compared to sunitinib alone, revealed an enhancement of the blockage of the VEGF pathway on renal tumor resulting in a decrease in neoangiogenesis and an increase in necrosis. 53 Recent clinical evidences suggest that use of ASI and ARB may be associated with improved outcomes in kidney cancer patients particularly when they are used with VEGF therapies. Three prior studies have reported on a significant association of ASI use (at baseline or within first 30 days of VEGF-targeted therapy) and survival for patients with mRCC using a VEGF-targeted therapy.…”
Section: Angiotensin System Inhibitors In Renal Cell Carcinomamentioning
confidence: 99%